Microbial Mats of the McMurdo Dry Valleys, Antarctica: Oases of Biological Activity in a Very Cold Desert - Sohm, Jill A.; Niederberger, Thomas D.; Parker, Alexander E.; Tirindelli, Joëlle; Gunderson, Troy; Cary, Stephen Craig; Capone, Douglas G.; Carpenter, Edward J. (Frontiers in Microbiology, 2020)
Cyanobacterial mats in the Antarctic Dry Valleys are photosynthetic microbial ecosystems living at the extreme of conditions on Earth with respect to temperature, light, water and nutrient availability. They are metabolically active for about eight weeks during the austral summer when temperatures briefly rise above freezing and glacial and lake melt waters are available. There is much to learn about the biogeochemical impact of mats in these environments and the microbial communities associated with them. Our data demonstrate that these mats attain surprisingly high rates of carbon (CO2) & dinitrogen (N2) fixation when liquid water is available, in some cases comparable to rates in warmer temperate or tropical environments. C and N2 fixation in Dry Valley mats in turn substantially elevate dissolved organic C and inorganic N pools and thereby promote enhanced microbial secondary production. Moreover, the microbial community fingerprint of these mats is unique compared with the more ubiquitous dry soils that do not contain mats. Components of the heterotrophic microbiota may also contribute substantially to N inputs through N2 fixation.